Anxiety And Writing Achievement Of Efl Learners: A Path Analysis - KHELALFA, Nawal; KELLIL, Mountassar Billah (جامعة الوادي - university of eloued, 2023)
Research has thus far provided inconclusive evidence for the extent to which foreign language writing anxiety is a determinant of writing outcomes. This study aimed to clarify the effects of anxiety by re-examining its role in the writing achievement of language learners. This was accomplished by examining its association with self-efficacy, a variable believed to be closely linked to anxiety and achievement. A total of 191 Algerian students of EFL (English as a Foreign Language) responded to a survey aimed at measuring writing anxiety and self-efficacy. In order to explain the relationship between the variables, the researchers constructed and tested a model using path analysis techniques via the Linear Structural Relationship (Lisrel) program. Results have revealed that second language writing anxiety is directly associated with second language writing achievement. Anxiety was also found to function as a significant mediator between writing self-efficacy and writing achievement. Some pedagogical implications are discussed.
Article .Ex Professo. Vol 08. N 01. Université d'El-Oued
Keywords: Second language writing anxiety ; self-efficacy; motivation ; effort ; writing.